The interrelations among tourism industry, social media, and technological innovation: A systematic review approach - Firman, Afrizal (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Technological approach affecting on tourism industry development is uncertainties from era to era. This study examines the impact of social media and technological innovation on tourism outcomes through a systematic review. Data were collected from three databases: EBSCO (1984-2019), Scopus (2005–2021), and Web of Science (2009-2020), using keywords such as technology innovation, digitalization, social media, and enhancing tourism industry outcomes. Quality assessment was performed using SPSS and Cohen’s Kappa statistics by two reviewers. Out of 156 articles initially screened, nine qualitative studies were included after further review. The findings indicate that social media platforms have the most significant impact on the development of the tourism industry. However, the study has limitations, including not exploring the impact of blockchain technology adoption. The concept of tourism has evolved into smart tourism, influencing tourist behavior through digital marketing, creative digital solutions, and digital payments. This has modernized and enhanced the tourism industry, requiring further efforts to meet tourist demands and expectations. Technologies like AI, IoT, VR, and AR are key factors in improving the tourism industry. To boost competitiveness and sustainable performance, stakeholders, governments, and tourism practitioners need to collaborate on developing strategies and technological innovations.